«VALIDITY» OR THE «SIGNIFICANCE» — 12 YEARS LATER - N.A. Zorin (Педиатрическая фармакология)
The consequences of misuse of the term «validity» in the Russian medical literature are presented. The hypothesis that the replacement of the term «statistical significance» by the widespread term «validity» depending on the context can lead to a distortion of the research perception in general is being checked. It is shown that the mechanisms of this process can be described in terms of the theory of the formation of mythological constructs of the French structuralism school, as well as on the basis of representations of memetics. The recommendations for researchers and editors of medical publications on the right and the best optimal use of those terms and the context language. Key words: scientific terminology, validity, significance, scientometrics, linguistic analysis, semantics, myths formation, memetics. (Pediatric Pharmacology. — 2011; 8 (5): 13–19.)